Solar Radiation Applications - Raphael Bello, Segun (IntechOpen, 2015)
Two essential components of solar energy which are derivable from the sun-radiant light (passive solar power) and heat (active solar powers) have been harnessed for decades using a range of continuously-evolving and cutting-edge technologies. Such technologies include solar heating, solar photovoltaics, solar thermal energy, solar architecture and photo emitters. Recently, there has been active research in solar energy resources due to improvements in solar panel geometry, photo-cell materials, glazing and panel orientation. Equally, more rigorous methods of modeling inter-reflections within curvilinear surfaces are now being evaluated for simplified analytical evaluations. Therefore, this book, Solar Radiation Applications, presents the outcomes of selective and classic works on the optimization of these essential fields in active solar energy research.